2007
DOI: 10.1161/strokeaha.107.484162
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Glutathione S-transferase Omega-1 Ala140Asp Polymorphism With Cerebrovascular Atherosclerosis and Plaque-Associated Interleukin-1α Expression

Abstract: Background and Purpose-Glutathione S-transferase omega-1 is a multifunctional enzyme. The Asp/Asp genotype of the Ala140Asp polymorphism of the GSTO1 gene has been alleged to increase the risk of vascular dementia. The objective of this study is to address the question of whether common vessel disorders known to cause vascular dementia are modified in their severity by this polymorphism. Methods-The severity and expansion of atherosclerosis in the circle of Willis vessels, cerebral small vessel disease, and ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 8 publications
2
21
0
Order By: Relevance
“…Increased lipoprotein (a), C-reactive protein, and plasminogen activator inhibitor-1 41 are other biomarkers associated with progression of ICAD. In an autopsy study, carriers of the glutathione S-transferase omega-1 Asp/Asp genotype were found to have more severe and widespread intracranial atherosclerosis than noncarriers, while there was no effect of the polymorphism on small vessel disease severity 42 . Among 40 Spanish patients with ischemic stroke secondary to ICAD, a higher endostatin/vascular endothelial growth factor (VEGF) ratio was associated with higher severity of stenosis (OR 15.7;CI 2.2-112.3), as well as a higher risk of recurrent events over a 13 month follow-up (HR 7.24;CI1.…”
Section: Risk Factors For Icadmentioning
confidence: 93%
“…Increased lipoprotein (a), C-reactive protein, and plasminogen activator inhibitor-1 41 are other biomarkers associated with progression of ICAD. In an autopsy study, carriers of the glutathione S-transferase omega-1 Asp/Asp genotype were found to have more severe and widespread intracranial atherosclerosis than noncarriers, while there was no effect of the polymorphism on small vessel disease severity 42 . Among 40 Spanish patients with ischemic stroke secondary to ICAD, a higher endostatin/vascular endothelial growth factor (VEGF) ratio was associated with higher severity of stenosis (OR 15.7;CI 2.2-112.3), as well as a higher risk of recurrent events over a 13 month follow-up (HR 7.24;CI1.…”
Section: Risk Factors For Icadmentioning
confidence: 93%
“…Since their first description, the Omega class GSTs have been investigated in relation to a number of biologically significant pathways and clinical disorders including drug resistance (21), Alzheimer disease (22)(23)(24), Parkinson disease (25), vascular dementia and stroke (26,27), and amyotrophic lateral sclerosis (28), the action of anti-inflammatory drugs (29), the disposition of arsenic (30), and susceptibility to chronic obstructive pulmonary disease (31)(32)(33) and cancer (34 -40). However, the mechanism by which the Omega GSTs mediate their effects in these diverse settings has not been clear.…”
mentioning
confidence: 99%
“…These include angiotensin converting enzyme polymorphism, plasma to vascular endothelial growth factor ratio, glutathione S-transferase, omega-1 gene polymorphism, and plasma homocysteine level [13,[29][30][31][32]. They exert their action via various mechanisms such as vascular endothelial injury, proliferation of vascular smooth muscle cell, and impairment of angiogenesis.…”
Section: Genetic Factorsmentioning
confidence: 99%